METACOGNITIVE AWARENESS OF PROSPECTIVE EFL TEACHERS AS PREDICTORS FOR COURSE ACHIEVEMENT: TEACHING ENGLISH TO YOUNG LEARNERS - Su Bergil, Ayfer (International Online Journal of Education and Teaching, 2020)
This study gives priority to investigate the metacognitive awareness levels of prospective English as a Foreign Language (EFL) teachers and the effects of it on prospective teachers’ Teaching English to Young Learners achievement which includes and also reflects their micro-teaching process occurring during this course. For this purpose, the participants of the study consist of the 3rd and 4th grade students studying in 2018-2019 academic year at Amasya University, Faculty of Education, English Language Teaching (ELT) Programme. 52-item Metacognitive Awareness Inventory was used as data collection instrument, and its relation with the teaching skills of micro-teaching in Teaching English to Young Learners course process were analyzed. As a method, qualitative and quantitative research methods were applied to the data. Based on the findings, it was observed that the prospective teachers, who are the teachers of future and expected to open the gate for learners to perceive the information profoundly, have these pre-condition skills at different levels. Therefore, it could be stated that the English teacher education process of faculties needs to be explored deeply by taking into consideration the fact that homogeneity in the qualities/characteristics of English language teachers is an urgent call to provide equal chances for the learners. Keywords: Metacognition, metacognitive awareness, teaching skills.